Open DataStack to power Government of Uttar Pradesh’s AgriStack - Mehrotra, N. (CGIAR System Organization, 2023)
The goals for an Agri stack for Uttar Pradesh should include: 1. Increase Agricultural Productivity: By providing farmers with actionable insight through access to real-time data on weather conditions, soil health, and crop yields, and help make better decisions about planting, irrigation, and fertilization. 2. Improve livelihoods: Improve farmers' livelihoods by connecting them with markets and buyers, and help them sell their produce at better prices. 3. Enhance Resilience: Improve financial resilience through insurance products as well as to climate change by identifying areas that are most vulnerable and using Data and information to protect their crops. 4. Digitization of Agriculture and farmers: The project should aim to digitize agriculture and farmers by creating a digital platform that allows farmers to access important information and connect with buyers and the government. 5. Improve the Agri economy and hence overall economic condition of Farmers: Increase agricultural productivity, profitability, and resilience for farmers and have a significant impact on the overall economy. 6. Enhancing Farmer Trust and Digital literacy: Improve the acceptability of digital solutions and technologies by the farmers through improved accreditation, validation of Ag Tech claims and improved digital literacy. 7. Balancing Farmers interests for Data confidentiality and economic benefit: Ensure that the Farmer data is not misused and the Farmers / State / National interests are protected. At the same time, while protecting confidentiality, ensure that Agri Data is leveraged for its economic potential and a regulated but commercially viable Agri Data market place is created across the Govt, Private sector and the Farmer.